The tight balance state and mechanism of disaster-resilient resources in karst small towns: a Chinese karst landform case study - Sicheng Wang; Dinglin Song; Mingming Gao (Scientific Reports)
Abstract Karst small towns globally face challenges due to limited disaster-resilient resources, making it difficult to handle increasingly severe disaster environments. Improving the efficiency of disaster-resilient resource utilization and maintaining a tight balance state of disaster-resilient resources (TBS) are crucial for enhancing disaster adaptability and resilience. This study used urban and disaster data from a representative karst region in China (2017–2021) to conduct a quantitative analysis of TBS in karst small towns, exploring the mechanisms and interactions within this state and identifying obstacle factors. Results show an average TBS of 0.355, indicating a low level with growing disparities among towns. The spatial pattern of TBS has shifted from “high in the south, low in the north” to a multi-center structure, with central towns exhibiting stronger resource siphoning compared to radiating and driving abilities. The Coupling Coordination Degree model shows high coupling but low coordination, with an average value of 0.56, suggesting moderate coordination. Enhancing subsystem coupling and coordination is essential for improving TBS and disaster adaptability. Obstacle factor diagnosis identifies Driving Forces as the main constraint, followed by Responses, States, Pressures, and Impact. Lack of disaster monitoring and early warning technologies increases socio-economic losses caused by disasters.